Energy - Wilson, Mitchell A.; Time-Life Books (New York : Time-Life Books, 1967)
Text and picture essays cover such aspects of energy as the movement of molecules, beat, chemical and electrical energy, Einstein's contributions, light, oil, and new sources of energy.
Includes bibliographical references (page 196) and index.
Donated By Akbar Ali Khan
Keywords: Power (Mechanics).; Power (Mechanics).; Technology